Conceptual paper presentation (technology) - Hasnah, Haron (Penerbit UMP, 2017)

(untitled)
This module focuses on what is meant by a conceptual paper and attempts to explain and illustrate the components of a conceptual paper. Components include problem statement, literature review, theory, theoretical framework and hypotheses development. The module concludes with an illustration of what a conceptual paper is.